Regional integration and labour law: a comparative analysis of the EU and Mercosur - Pucheta, Mauro Leonardo (2019)
The emergence of transnational production networks and the expansion of multinational companies, as well as the development of digitalisation – all elements of the globalisation phenomenon – have largely contributed to render ineffective national labour laws. This major shift has modified the context in which labour relationships take place. States and their boundaries constitute no longer the only reference framework for labour regulations. Employment relationships have radically changed in terms of time, place, and space. Current labour laws consist of overlapping national, regional, international and even ‘private’ regulations. Regional legal orders have been presented as complementary systems developed to address the deficiencies faced by national systems. However, the synergy between transnational economic integration and the promotion of labour values and protection of labour rights at the regional level has been less clear. This thesis explores whether there is a unique methodology of regional integration in the labour sphere, or diverse ways to regulate labour matters at the regional level are possible depending on the economic, social, political and institutional contexts. To answer this question, it analyses the EU and Mercosur cases. This thesis rejects a Eurocentric approach, and drawing on recent regional integration literature, embrace a perspective whereby both regional organisations are understood as diverse and autonomous experiences, which have developed their own institutional and legal systems. Nonetheless, this has not entailed the dismissal of the European experience when examining Mercosur. The EU and Mercosur are regional integration organisations characterised by both structural differences and some similar purposes. This thesis examines comparatively the institutional and legal, as well as the economic spheres of both organisations. The EU remains indisputably the most developed and autonomous regional organisation. Its labour dimension has partially reshaped and complemented national labour laws. However, this thesis argues that there is no a unique paradigm of integration. Drawing on this approach, it suggests that even though developing supranational institutions may more speedily advance the adoption and integration of regional labour laws, it is not a feasible option in the current context of Mercosur. This does not mean that the development of a successful regional labour dimension is not possible. This thesis concludes that regional and national actors can further develop the existing intergovernmental Mercosur labour dimension.